An Unusual Phase Transition Driven by Vibrational Entropy Changes in a Hybrid Organic–Inorganic Perovskite. (20th June 2018) - Wei, Wenjuan; Li, Wei; Butler, Keith T.; Feng, Guoqiang; Howard, Christopher J.; Carpenter, Michael A.; Lu, Peixiang; Walsh, Aron; Cheetham, Anthony K.
Abstract: The driving forces for the phase transitions of ABX3 hybrid organic–inorganic perovskites have been limited to the octahedral tilting, order–disorder, and displacement. Now, a complex structural phase transition has been explored in a HOIP, [CH3 NH3 ][Mn(N3 )3 ], based on structural characterizations and ab initio lattice dynamics calculations. This unusual first‐order phase transition between two ordered phases at about 265 K is primarily driven by changes in the collective atomic vibrations of the whole lattice, along with concurrent molecular displacements and an unusual octahedral tilting. A significant entropy difference (4.35 J K −1  mol −1 ) is observed between the low‐ and high‐temperature structures induced by such atomic vibrations, which plays a main role in driving the transition. This finding offers an alternative pathway for designing new ferroic phase transitions and related physical properties in HOIPs and other hybrid crystals.